Formulasi Dan Uji Aktivitas Tabir Surya Sediaan Cream Ekstrak Batang Pohon Pisang Kepok (Musa Paradisiaca L.) - Zakiyatul Hamida; Siti Marita Ubaid; Desy Dwi Jayanti; Panji Ratih Suci; Cikra Ikhda N.H.S (Journal of Educational Innovation and Public Health, 2024)
The trunk of the kepok banana tree contains flavonoids that have activity as a sunscreen that can protect the skin from the adverse effects of UV rays. This study aims to formulate and determine the SPF value of the cream preparation of banana kepok tree tree extract (Musa paradisiaca L) which meets the requirements of good physical quality as a sunscreen. The method used is experimental research consisting of making maceration method extracts with 70% ethanol solvent. The resulting extract is formulated with a cream base formula with extract concentrations of 30% and 40%. The study was analyzed using ANOVA test and SPSS software. The results showed that the formulation of sunscreen cream extract of banana kepok tree trunk extract (Musa paradisiaca L) with concentrations of 30% and 40% showed good physical quality with the effectiveness of SPF at concentrations of 30% and 40% was 3.1 and 4.7 in the moderate protection category without any reference or formula. Based on the results of the article's research, it was concluded that the extract of the banana kepok tree trunk (Musa paradisiaca L) which was formulated as a cream has good physical quality as a sunscreen and based on the ANOVA test, one factor showed a difference in concentration affecting the SPF value obtained.